The Existence Of The Dayah Jeumala Amal Business Unit Towards Surrounding Communities In Lueng Putu, Pidie Jaya - Muazzam, Andri; Musfiana, Musfiana; Razak, A; Mustofa, Achmad (Economic Education and Entrepreneurship Journal, 2023)
This study aims to determine the existence of the Dayah Jeumala Amal business unit by knowing the forms of economic empowerment carried out by the dayah business unit for the community and to determine the amount of benefits received by the surrounding community in Lueng Putu, Pidie Jaya Regency. This research uses a qualitative approach method. The subjects of this study were the director of the dayah business unit, financial manager, store and canteen manager, and the community who partnered with the Jeumala Amal Dayah business unit in meeting the needs of the santri. Data collection techniques using library research and interviews. While data analysis uses the Miles and Huberman model analysis, namely data reduction, data presentation and drawing conclusions. The results of research related to the existence of the Dayah Jeumala Amal business unit, namely economic empowerment carried out by Dayah Jeumala Amal through the Dayah Jeumala Amal business unit by providing space for the community to participate in meeting the needs of students are able to have a positive impact, this is in line with the benefits provided by the unit Dayah businesses such as helping to increase people's income so that they can help people meet their daily needs, create jobs and business opportunities for the surrounding community in the hope of reducing unemployment and reducing poverty. Therefore, as a collective effort in alleviating economic problems, the Dayah Jeumala Amal business unit continues to improve and transform with a more professional management system.Keywords: Business Community, Business Unit, Dayah Jeumala Aaml Business Unit, Islamic Boarding School DOI: http://dx.doi.org/10.23960/E3J/v6i1.104-109